EVALUASI KEPUASAN TAMU HOMESTAY MELALUI ONLINE TRAVEL AGENT – OTA: STUDI NETNOGRAFI PADA HOMESTAY DI KUTA MANDALIKA - Muhammad Sultan Hali; Abdul Hanan; Rahman Hidayat (Bajang Institute, 2023)
Online Travel Agent – OTA is a stakeholder that has a very significant role in the number of guests who will stay using the homestay. Mandalika is a destination that has a lot of homestay perpetrators, where they make accommodation efforts to support the amount of accommodation that guests need. However, this can have a positive or negative impact on the destination image of the services and facilities available. The study uses a netnographic study where data is taken from the application as well as the OTA and Homestay online sites analyzed for the evaluation of guest satisfaction. With this approach found on OTA that the satisfaction of guests staying in a homestay in the area of Mandalika can be evaluated from the hygiene, services and hospitality of facilities and property facilities. This survey reveals based on the guest satisfaction theory that the homestays with OTA developers require hygiene standards and facilities as well as services that can be displayed on the OTA in detail to meet the expectations of the guests who book through OTA or other online system